The Heritage of F.M. Dostoevsky and the Problem of Moral Interpretation of the Dogma of the Trinity in Russian Theology XIX – First Third of XX Century (Article No. 2) - Anastasia G. Gacheva (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2020)
The article is devoted to the theology of F.M. Dostoevsky and specifically to the understanding of the dogma of the Holy Trinity. Dostoevsky understands the undivided unity of the Divine hypostases as a model of perfect interaction among individuals, a norm for social unions, a model for all-united humanity, where the truth of the individual is reconciled with the truth of the whole. The diary fragments of 1864 “Masha lies on the table…” and “Socialism and Christianity” are analyzed from the point of view of Trinitarian problems. The triple unions presented in the writer’s early works are considered in the context of their proximity/distance from the Divine prototype. According to Dostoevsky, when a person goes towards another, addressing him or her as a person, not as a function, it carries the secret of the Trinity within its own life, confessing it not just in words, but in deeds. For the author, the distortion of the Trinity principle is atomicity and dualism; its embodiment is the image of “an expanding family”.